2016
DOI: 10.1186/s13039-016-0263-7
|View full text |Cite
|
Sign up to set email alerts
|

Target fluorescence in-situ hybridization (Target FISH) for plasma cell enrichment in myeloma

Abstract: BackgroundCytogenetic abnormalities are important prognostic markers in plasma cell myeloma (PCM) and detection is routinely performed by interphase fluorescence in-situ hybridization (FISH) with a panel of probes after enrichment of the plasma cells in the bone marrow specimen. Cell sorting by immunomagnetic beads and concurrent labeling of the cytoplasmic immunoglobulin are the usual enrichment methods. We present an alternative method of plasma cell enrichment termed Target FISH, which is an automated syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Data from recent studies in China also showed that the incidence of t(14;16) was only 0.8–6.7% among newly diagnosed MM patients [ 26 28 ], and the detection rate of t(14;16) was 1.2% in recently diagnosed MM patients [ 26 ]. A recent study from Hong Kong showed the absence of t(14;16) among 40 MM cases [ 29 ]. Translation of t(14;16) has also been observed in patients with MGUS, with the detection rate of approximately 5% [ 1 , 30 ], suggesting that the chromosomal translation may be involved in the early stages of the disease; however, its impacts on disease prognosis remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Data from recent studies in China also showed that the incidence of t(14;16) was only 0.8–6.7% among newly diagnosed MM patients [ 26 28 ], and the detection rate of t(14;16) was 1.2% in recently diagnosed MM patients [ 26 ]. A recent study from Hong Kong showed the absence of t(14;16) among 40 MM cases [ 29 ]. Translation of t(14;16) has also been observed in patients with MGUS, with the detection rate of approximately 5% [ 1 , 30 ], suggesting that the chromosomal translation may be involved in the early stages of the disease; however, its impacts on disease prognosis remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of cytogenetic abnormalities was performed on myeloma cells in the bone marrow by FISH, as previously described 38 . Interphase FISH was performed on slides for the examination of high-risk (HR) karyotypes, including t(4;14), t(14;16), del(17p), and amp(1q21), by IGH/FGFR3 DF FISH Probe kit (Vysis, USA), IGH/MAF DF FISH Probe kit (Vysis, USA), TP53/CEP17 FISH Probe kit (Vysis, USA), and CKS1B/CDKN2C (P18) amplification/deletion probe (Cytocell) respectively, in accordance with the International Myeloma Workshop Consensus recommendation.…”
Section: Methodsmentioning
confidence: 99%
“…FISH, in contrast, requires the cell to be in interphase, the phase of the cell cycle in which the majority of cells are at in a given point of time [59]. FISH detection rate of cytogenetic abnormalities in plasma cell dyscrasia can further be enhanced with plasma cell enrichment, by increasing the number of the plasma cells collected in the bone marrow aspirate undergoing analysis [60][61][62].…”
Section: Fluorescent In-situ Hybridization (Fish)mentioning
confidence: 99%